Fit für die Zukunft: Phänomenologische Vignetten und Schulentwicklung (Pedagogical Horizons, 2023)
In recent years, national and international in school development has increased significantly. The individual school, which is seen as the driving force, has a special position. Against the background of Rolff's school development model, this article is dedicated to the (further) development of teaching in order to systematically initiate school development. For this purpose, a phenomenologically oriented approach to school development is used, which uses vignettes as instruments. An example vignette illustrates how, with their help, school development processes can be set in motion at individual schools, which serve to improve learning, teaching and pedagogical action.
Keywords: School development, individual school, school learning, phenomenological vignette, phenomenology